2016
DOI: 10.1089/cap.2015.0060
|View full text |Cite
|
Sign up to set email alerts
|

Switch in Therapy from Methylphenidate to Atomoxetine in Children and Adolescents with Attention-Deficit/Hyperactivity Disorder: An Analysis of Patient Records

Abstract: Objective: The purpose of this study was to investigate therapy switching from methylphenidate (MPH) to atomoxetine (ATX) in a clinical sample of Danish children and adolescents with attention-deficit/hyperactivity disorder (ADHD); specifically, to determine the duration of MPH treatment before switching to ATX, and the reasons leading to a switch in therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…By contrast, in the US amphetamine salts have grown from 35.5% to 42.1%, partly due to recent expanded use of lisdexamfetamine products (initially approved in the US in 2007). Atomoxetine use has grown in European countries mainly in Denmark (Warrer et al, 2016), but has decreased in the US. Centrally acting alpha-agonists, e.g.…”
Section: Product Preferencesmentioning
confidence: 99%
“…By contrast, in the US amphetamine salts have grown from 35.5% to 42.1%, partly due to recent expanded use of lisdexamfetamine products (initially approved in the US in 2007). Atomoxetine use has grown in European countries mainly in Denmark (Warrer et al, 2016), but has decreased in the US. Centrally acting alpha-agonists, e.g.…”
Section: Product Preferencesmentioning
confidence: 99%
“…In a Danish study, among 55 children/adolescents with ADHD prescribed MPH first line, 36.0% switched treatments during the first 6 months (Warrer et al, 2016). A variety of factors likely contributed to the switch, including adverse effects, non-optimal day coverage, lack of efficacy, patient/parental preferences, and non-compliance (Warrer et al, 2016). Another Danish study found that, in 2000, 20.8% of patients discontinued ADHD medication (limited to MPH and ATX) within 6 months; this had reduced to 12.5% by 2012 (Pottegard et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that, among patients prescribed a stimulant first line, 24.0% switched to another agent within 60 days, mostly because of poor tolerability (Biederman et al, 2021). In a Danish study, among 55 children/adolescents with ADHD prescribed MPH first line, 36.0% switched treatments during the first 6 months (Warrer et al, 2016). A variety of factors likely contributed to the switch, including adverse effects, non-optimal day coverage, lack of efficacy, patient/parental preferences, and non-compliance (Warrer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The same format was used to independently extract data from the articles, compare the data, and repeat the extraction and comparison of inconsistent items. Specifically, the following information was extracted from each study: study design, first author, country in which the study was performed, year of publication, number of events (the group of participants with an event) and total (participant groups), event term, follow-up period (year), and drug duration (month) (Table 1) [30][31][32][33][34][35][36][37][38][39].…”
Section: Data Extractionmentioning
confidence: 99%